Localisation of proteins of iron metabolism in the human placenta and liver. - Bastin, J; Drakesmith, H; Rees, M; Sargent, I; Townsend, A (2006)
Two anatomical sites that are important in human iron metabolism are the liver and placenta. Liver macrophages recycle iron from erythrocytes, and the placenta transfers iron from the mother to the fetus. The cellular distribution of proteins involved in iron transport in these two sites was studied. Transferrin receptor-1 (TfR1) and Ferroportin (FPN) expression was found on the placental syncytiotrophoblast (STB) and were polarised such that TfR1 was on the apical maternal-facing membrane and FPN was on the basal fetal-facing membrane, consistent with unidirectional iron transport from mother to fetus. Ferritin was strongly expressed in the stroma, suggesting that fetal tissue can store and accumulate iron. HFE was on some parts of the basal STB and, where present, HFE clearly colocalised with FPN but not TfR1. In the stroma, both HFE and FPN were present on CD68+ Hofbauer macrophage cells. In liver, the location of HFE is controversial. Using four mouse monoclonals and two polyclonal sera we showed that the pattern of HFE expression mirrored the distribution of CD68+ macrophage Kupffer cells. FPN was also most strongly expressed by CD68+ Kupffer cells. These findings contribute to understanding how iron is transported and stored in the human placenta and liver.